Management of Natural Resources for Sustainable Economic Development in Arunachal Pradesh : Employment Generation Issues - Lall, Stuti (Journal of Soil and Water Conservation, 2022)
The approach for development of natural resource based employ- ment generation particularly in north-eastern states of the country is described in this mere In this connection, role of State Land Use Board (SLUG) is highlighted for overall development and income-employment generating activities particularly in Arunachal Pradesh.